2022
DOI: 10.1161/hypertensionaha.122.18657
|View full text |Cite
|
Sign up to set email alerts
|

Ang II (Angiotensin II)–Induced FGFR1 (Fibroblast Growth Factor Receptor 1) Activation in Tubular Epithelial Cells Promotes Hypertensive Kidney Fibrosis and Injury

Abstract: Background: Elevated Ang II (angiotensin II) level leads to a range of conditions, including hypertensive kidney disease. Recent evidences indicate that FGFR1 (fibroblast growth factor receptor 1) signaling may be involved in kidney injuries. In this study, we determined whether Ang II alters FGFR1 signaling to mediate renal dysfunction. Methods: Human archival kidney samples from patients with or without hypertension were examined. Multiple genetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Ang II is an important active product of the renin-angiotensin-aldosterone system. It stimulates the release of epinephrine and norepinephrine, constricts blood vessels, and increases blood pressure [ 22 , 23 ]. Ang II promotes synthesis and inhibits degradation of ECM, leading to accumulation of ECM and ultimately inducing renal [ 24 ], pulmonary [ 25 ], and myocardial fibrosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ang II is an important active product of the renin-angiotensin-aldosterone system. It stimulates the release of epinephrine and norepinephrine, constricts blood vessels, and increases blood pressure [ 22 , 23 ]. Ang II promotes synthesis and inhibits degradation of ECM, leading to accumulation of ECM and ultimately inducing renal [ 24 ], pulmonary [ 25 ], and myocardial fibrosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that Gpr126 is expressed during kidney development [11,12]. To determine whether Gpr126 expression is altered during kidney disease, we performed RT-PCR analyses measuring the Gpr126 RNA levels in kidneys from animal models with mild (Ang II treatment, model of hypertensive nephropathy, mouse [24]) and severe kidney damage (I/R, model of AKI, rat [25]; UUO, model of interstitial fibrosis occurring in chronic renal failure, mouse [26]). While the Ang II treatment resulted in a modest increase (1.5-fold), I/R and UUO resulted in a marked upregulation of Gpr126 expression (2.5-and 8-fold, respectively, Figure S1).…”
Section: Gpr126 Expression Is Increased In a Model Of Kidney Fibrosis...mentioning
confidence: 99%
“…Angiotensin‐II (Ang‐II) is a small peptide hormone derived from angiotensinogen through the enzymatic cleavage cascade (Yi et al, 2022). Several studies have demonstrated that Ang‐II is a profibrotic contributor and plays role in the pathogenesis of kidney fibrosis (Lyu, Li, Wu, & Hao, 2019; Wang et al, 2018; Xu et al, 2017, 2022). Ang‐II mediates kidney fibrogenesis by TGF‐β/Smad3 pathway activation (Lyu et al, 2019; Wu, Wang, Yu, & Lan, 2022).…”
Section: Emt and Kidney Fibrosismentioning
confidence: 99%